Particle-yield modification in jetlike azimuthal dihadron correlations in Pb-Pb collisions at √sNN=2.76 TeV - Aamodt, Kenneth; Busch, Oliver; Engel, Heiko; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lara Martinez, Camilo Ernesto; Lohner, Daniel; Mercado Pérez, Jorge; Oyama, Ken; et al. (Physical review letters, 2012)
The yield of charged particles associated with high-pt trigger particles (8<pt<15 GeV/c) is measured with the ALICE detector in Pb-Pb collisions at √sNN=2.76 TeV relative to proton-proton collisions at the same energy. The conditional per-trigger yields are extracted from the narrow jetlike correlation peaks in azimuthal dihadron correlations. In the 5% most central collisions, we observe that the yield of associated charged particles with transverse momenta pt>3 GeV/c on the away side drops to about 60% of that observed in pp collisions, while on the near side a moderate enhancement of 20%-30% is found.